Al‐Ni‐NiO Pyrotechnic Time‐Delays. Issue 4 (14th February 2020) - Guo, Shasha; Focke, Walter W.; Tichapondwa, Shepherd M.
Abstract: The time delay elements in conventional mine detonators comprise pyrotechnic compositions pressed in aluminum tubes. Thermite and intermetallic reactions offer the possibility of greener alternatives for current heavy metal‐based compositions. Unfortunately, the high reaction temperatures associated with conventional thermites cause operational failures due to the melting of the metal housings. Similarly, it is difficult to achieve sustained burning with intermetallic systems alone. Combination thermite‐intermetallic systems may offer a solution to both problems. The concept is illustrated through ternary compositions based on powder mixtures of aluminum, nickel and nickel oxide. Progressive dilution of the primary thermite reaction, 5 Al+3 NiO→Al2 O3 +3 AlNi, with the intermetallic reaction, Al+Ni→AlNi, smoothly reduced the adiabatic reaction temperature by as much as 800 K simultaneously maintaining consistent burn behavior inside both glass and lead tubes. However, in the process the burning rate gradually decreased from ca. 190 mm s −1 to as low as 23 mm s −1 . Abstract :